Sustained suppression of enterohepatic circulation of mycophenolic acid by antimicrobial‐associated diarrhea in a kidney transplant recipient with Crohn's disease: A case report. Issue 6 (5th June 2022) - Tanaka, Ryota; Matsumoto, Asami; Tatsuta, Ryosuke; Ando, Tadasuke; Shin, Toshitaka; Mimata, Hiromitsu; Itoh, Hiroki
Abstract: Mycophenolic acid (MPA) undergoes enterohepatic circulation. A kidney transplant patient on mycophenolate mofetil was treated with tazobactam/piperacillin for pyelonephritis, and developed antimicrobial‐associated diarrhea. Consequently, the MPA trough level decreased by approximately 90%. Furthermore, it took approximately a month for the MPA level to normalize even after diarrhea had resolved. Abstract : If diarrhea develops following the initiation of broad‐spectrum antibiotics in kidney transplant patients, mycophenolic acid trough level can decrease remarkably, and it could take some time to recover to the level before diarrhea.